Conformational Analysis and Near-Infrared-Induced Rotamerization of Malonic Acid in an Argon Matrix - Maçôas, Ermelinda M. S. (2000)
Relative energies and vibrational spectra of the conformational states of a malonic acid monomer (HOOCCH2COOH) were calculated using various levels of approximation [Hartree−Fock (HF), Møller−Plesset to second order (MP2), and B3LYP density functional theory (DFT)]. The calculations predict the existence of six different conformers according to skeletal C−C bond and O−H bond rotation. Three conformers are found with energies close enough to enable their spectroscopic observation. The lowest-energy conformer (I) shows a nearly planar structure with an OH···OC intramolecular hydrogen bond closing a six-member ring. The second- and third-lower energy conformers (II and III) differ from the conformational ground state by less than 5 kJ mol-1. Conformers II and III adopt a cis arrangement around the C−O bonds: conformer II exhibits the two carbonyl bonds in a nearly orthogonal arrangement, with one carboxylic group in the plane containing the carbon atoms, whereas in conformer III (C2 symmetry), the carbonyl bonds make a dihedral angle of ca. 120°, and both carboxylic groups are placed out of the plane containing the skeletal carbons. Their relative energy is predicted by the highest-level calculations to be ca. 1 kJ mol-1. The theoretical predictions agree with the analysis of the infrared spectra of monomeric malonic acid isolated in a solid argon matrix, where the presence of the three above-mentioned conformers was unequivocally identified. Narrowband tunable irradiation in the near-infrared region was found to promote efficiently the interconversion between the experimentally observed conformers.